(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
In the article, from the point of view of formation, the basis of professional culture is the social, spiritual and moral views of the specialist, the ability to recognize work and professional activity as a value, professional knowledge, skills, qualifications, experience and the ability to apply it in practice, the specialist’s intellectual, psychological, physiological , on the basis of the fact that professional competence is the level that determines their spiritual-moral maturity, positive attitude to professional activity, the possession of qualities, on the basis of the priority of deciding on a positive attitude to professional activity, ensuring and effective organization of their intellectual, psychological, physiological, spiritual-moral maturity at a high level is its organizational, methodical and practical, correct, rational organization, separate components of professional pedagogical culture are individual psychological characteristics, the professional culture of each pedagogue has uniqueness, individuality and uniqueness along with the individual general characteristics of the personality of the pedagogue, high level issues of psychological and pedagogical knowledge, pedagogical direction, culture of cognitive activity, and culture of pedagogical thinking are interpreted